The Last Straw :Diary of a Wimpy Kid - "Kinney, Jeff" (New York; Puffen Books, 2009)
Middle-schooler Greg Heffley nimbly sidesteps his father's attempts to change Greg's wimpy ways until his father threatens to send him to military school
Keywords: Diaries Fiction